PENGARUH KOMPENSASI, LIGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA GURU TIDAK TETAP DI PAUD SE-KOTA MATARAM - Nur Adni Fadilah Putri; Achmad Rasyad; Sutarno Sutarno; Imron Arifin (Jurnal Ilmiah Akuntansi Indonesia, 2022)
Non-permanent teachers who work in Early Childhood Education institutions do not yet have an appropriate salary standard, especially in the Mataram city area. The existence of a good, harmonious and conducive work environment is one of the factors in determining performance. providing motivation is one of the references so that teachers can work optimally so as to achieve the targets imposed by the institution. This study aims to 1) determine the effect of compensation on the performance of precarious teachers in PAUD in Mataram, 2) determine the effect of the work environment on the performance of precarious teachers in PAUD in Mataram, 3) determine the effect of work motivation on the performance of precarious teachers. in PAUD in the city of Mataram. This type of research is quantitative associative with a sample of non-permanent teachers in PAUD spread across the city of Mataram. The data collection method used a survey through filling out a questionnaire on a google form with a Likert scale of 1-5 and data analysis using SmartPLS 3.0. The results of hypothesis testing found that all variables, namely compensation, work environment, and work motivation had a positive and significant effect on the performance of non-permanent teachers with P-Value values of 0.000, 0.000, and 0.008 where all values were 0.05. Thus, the higher the compensation, a good work environment, and high work motivation, the performance of non-permanent teachers in PAUD throughout the city of Mataram will also increase.